HUBUNGAN PRESTASI BELAJAR PENGAJARAN MIKRO DAN PROGRAM PENGALAMAN LAPANGAN DENGAN KESIAPAN MENJADI GURU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN - Hafiidhiya Janata Areisy; Muhammad Akhyar; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
This aims of this research are to determine the relationship of student micro teaching-learning achievement with student readiness to be a teacher.  An educational internship experience is essential to be analyzed as being a teacher.  The study population was 69 active students. Fifty-eight students taken as samples were determined by simple random sampling technique. The documentation method is used to analyze micro teaching and PPL learning achievement variables. The variable readiness to become a teacher is obtained through the questionnaire method. Various tests were carried out with the help of the SPSS Version 21.0 program. Normality tests, linearity tests, and multicollinearity tests were carried out as test prerequisites. The data analysis technique uses partial correlation and multiple linear regression with a significance level of analysis of 5%. The results of the study show that the student learning achievement of microteaching on the readiness to be a teacher has a positive and significant relationship. Student Internship experience influences the readiness to be a teacher. The learning achievement of microteaching and Student Internship experience is considered to make big effect for being a teacher.  Keywords: Learning achievement in Microteaching, learning achievement in Field Experience Program, preparedness to become teachers